EVALUATING THE EFFECTIVENESS OF GOVERNMENT SUPPORT PROGRAMS FOR THE EXPORT OF FARM PRODUCTS - Tursunqulov Golib Shavkat ugli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article empirically evaluates the effectiveness of state support programs aimed at promoting agricultural exports by farm enterprises in Uzbekistan. The study analyzes the relationship between agricultural export volumes, the participation of farm enterprises in export activities, and the key financial and institutional support mechanisms provided by the state. The empirical analysis is based on official statistical data for the period 2018–2024, survey results obtained from farm enterprises in Samarkand region, and relevant regulatory and legal documents. Panel regression, Difference-in-Differences (DiD), and multivariate regression methods are employed to assess the impact of state support measures. The results indicate that subsidies, preferential loans, logistics support, and certification assistance have a positive and statistically significant effect on agricultural export volumes. However, this effect is more pronounced for large and organizationally advanced farm enterprises, while small farms continue to face substantial constraints related to logistics, certification costs, and access to market information. The findings provide important policy-relevant insights for improving the effectiveness, targeting, and inclusiveness of agricultural export support policies in Uzbekistan.